Diseño de una secadora de café a través de un sistema de aire acondicionado. - Conde Rojas, César Orlando. (2016)
This thesis aims to develop the design of a coffee machine dryer by forced air for a farm located in the Espíndola Canton of the Amaluza city, this farm has an annual production of 12000 kg of coffee. The harvest of the farm, mature progressively for this reason it should be harvested about 500 kg daily giving a total of 12 days of harvest. It is essential drying of this product so it is desirable to develop a machine that simplifies the work and therefore labor. To resolve this need is designed a coffee dryer by forced air. This design includes the selection of fan and heat exchanger electric heat which supplies hot air so that the coffee can dry within a short time because the traditional method of drying in rainy times is difficult and makes it difficult the drying and for this reason the product is more expensive. To develop the calculations of this design were used thermodynamic concepts to calculate the necessary energy that must have the heat exchanger, the calculation of the pressure losses in each accessory is also made to hereby conclude fan capacity to supply air into the drying chamber. After design calculations made of the dryer coffee has been obtained the following results. A heater of 21 kW for heating air, a fan 250 W, a pipeline which are composed of the following accessories: an elbow 90 ° rectangular and expansion. The bed of coffee is designed with a rack to allow the passage of hot air, and the whole system is insulated with Styrofoam (expanded polystyrene).